Re-examining the New "Greeneration" behaviors: How Does the Sequential Mediation role of Green Word of Mouth and Green Trust affect Green Purchase Intention among Generation Z? - Rahmawati; Hidayati, Nur; Srinin, Wathanan; Taufiqurijal, Ahmad (Jurnal Manajemen Teori dan Terapan| Journal of Theoretical and Applied Management, 2024)
Objective: This study explores whether and how the Z generation's perspective toward greenwashing perceptions influences their green purchasing intentions through the underlying green trust and green word of mouth. Design/Methods/Approach: We used purposive sampling to enroll research respondents. A total of 262 Z generation respondents met the criteria, and the partial least squares technique was applied for data analysis. Findings: Greenwashing has no significant effect on green purchase intention. However, green trust and green word of mouth significantly affect green purchase intention. We also examine the sequential mediation of green trust and green word of mouth in the relationship between greenwashing and green purchase intention and the result is significant. Originality/Value: This research provides unique and contribution by investigating the sequential intervening effect in the greenwashing – green purchase intention relationship. Practical/Policy implication: This article helps policymakers to develop policies that support the consumption of green products, fight greenwashing, and increase public awareness about green products. For marketers, it provides insights on how to increase green purchase intention through strategies based on word of mouth and green trust.